(untitled) (Iranian Journal of Kidney Diseases, 2011)
Introduction. The aim of the study was to assess the validity and reliability of the SF-12 questionnaire in a sample of Iranian patients undergoing hemodialysis. Materials and Methods. One hundred and forty-four hemodialysis patients were included from dialysis centers in Zanjan, Iran, and were asked to complete the SF-12 and SF-36 questionnaires. An initial test-retest reliability evaluation was performed on a sample of 70 patients from the total group, with a retest interval of 14 days. Reliability was estimated by internal consistency and validity was assessed using known-group comparisons and construct validity on the patient group as a whole. A linear regression analysis was used to assess any variation in the physical component summary and mental component summary scores of the SF-36 with the respective component summary scores of the SF-12. In addition, the factor structure of the questionnaire was extracted by performing a confirmatory factor analysis. Results. Cronbach alpha for physical and mental component summaries were 0.89 and 0.90, respectively. The SF-12 showed a good discriminatory ability between subgroups of patients based on demographic and clinical variables. The confirmatory factor analysis for the original two-factor structure showed a good fit index (chi2 = 23.30, degrees of freedom = 13), goodness-of-fit index = 0.96, and root mean squared error of approximation = 0.079). Conclusions. In general, the SF-12 has good psychometric properties and can be used as a shorter version of the SF-36 questionnaire in future studies involving Iranian patients undergoing hemodialysis.